Zaznavanje korupcije v Sloveniji - Lipar, Sonja (IB revija (Ljubljana), 2018)
This article analyses the perception of corruption in the public sector in Slovenia among public utility services users in Slovenia. A comparison is also made for Slovenia based on data from Transparency International, as obtained in previous international surveys. For this purpose, a special own survey was conducted on perceptions of the corruption of public officials. The Global Corruption Index questionnaire has been used, following repeated use in international research. The research has shown that public services users have not perceived major changes in the level of corruption and that the level of corruption in Slovenia during the most recent years has remained at a similar level. The perception of change in the level of corruption in Slovenia does not depend on the statistical region of permanent residence, nor on the age of public service users. However, it does depend on genders and on types of public services.
Keywords: javni sektor; javno mnenje; korupcija; Slovenija; svetovni (globalni) indeks korupcije